New Lithuanian compound personal names with open first member - Sinkevičiūtė, Daiva (Baltistica, 2023)
In the sources of the 15th–18th centuries, 20 new personal names were found whose first stem is an open syllable, whereas the second stem was attested in other compound names: Bùtartas, Čióbutkis, Daũrimas, Dãvinas, Dýbutas (or Dìbutas), Dýrimas (or Dìrimas), Dótautas, Eĩdaugas, Eĩjotas, Gãbutas, Gaĩgailas, Gẽtartas, Lìgailas (or Lýgailas), Naĩgailas, Nẽkantas, Saĩtautas, Taĩgailas, Tóliudas, Tùdaugas and Výbutas. Most of them are typically Lithuanian first and second stems, whereas other combinations are rarer. Thus, before the consolidation of Christian personal names, new names were normally made with Baltic stems, to which elements of the Lithuanian lexicon were attached. The new names not only add new examples to the already existing stock of common stems, but they are also important for the consolidation of the rare stems čio-, butk-, dy- (or di-), to-, tu-. The name Taĩgailas clearly attests the stem tai-. The stems di-, ly-, tu-, like dau-, dy-, ge-, are most likely secondary. They originated in the reanalysis of the stems of other compound names that were shortened through assimilation.